The global grapevine : why rumors of terrorism, immigration, and trade matter - Fine, Gary Alan.; Ellis, Bill, 1950- (New York ; Oxford : Oxford University Press, 2010)
'The Global Grapevine' documents how Americans grapple with the new global world through everyday thoughts & conversations, & the rumors they spread. Focusing on the threat posed by terrorism, the impact of immigration, the risks involved in international trade & the dangers faced by naive tourism, the book offers a broad survey.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Rumor; Globalization -- Social aspects